Terapi Audio dengan Murottal Alquran Terhadap Perilaku Anak Autis: Literature Review - Anam, Akhyarul; Khasanah, Uswatun; Isworo, Atyanti (Fakultas Ilmu-ilmu Kesehatan Universitas Jenderal Soedirman, 2019)
Introduction. Child auitism has a disorder in behavior, communication, social interaction and unstable emotions. Austism is a syndrome that results from complex muscle damage and neurodevelopmental disorders. Intervention to the behavior of children with autism can be done by providing murottal audio therapy Alquran.Objective. this study aimed to examine the effect of audio therapy with murottal Alquran on the behavior of austistic children.Methods. Article searches conducted electronically using several databases: Proquest, PubMed, Mendeley, and Google Scholar since 2013-2017. Keywords used are